Personality and online environment factors differ for posters, trolls, lurkers, and confessors on Yik Yak. (1st April 2018) - Seigfried-Spellar, Kathryn C.; Lankford, Claire M.
Abstract: Anonymous social media applications, such as Yik Yak, continue to rise in popularity, but little research has examined the individual differences and influence of online environment on different posting behaviors. 173 undergraduate students completed an anonymous online survey assessing the dark-triad, sadism, the five-factor model, online environmental factors, and different behaviors on Yik Yak (i.e., posting, trolling, confessing, lurking). Results suggested different personality and environmental factors were associated with the various posting behaviors. Trolls scored significantly higher on psychopathy, online acceptability of prejudiced comments, and lower on agreeableness; confessors scored significantly higher on neuroticism, Machiavellianism, feelings of reduced accountability online, and lower on social moral values. In contrast, lurkers scored significantly higher on conscientiousness and lower on Machiavellianism. By examining these different posting behaviors, it may be possible to identify and deter at-risk youth through education on being a good digital citizen. Highlights: Trolls scored higher on psychopathy and acceptability of prejudiced comments online. Confessors scored higher on neuroticism, Machiavellianism, and low accountability. Lurkers scored higher on conscientiousness and lower on Machiavellianism. Higher scores on acceptability of prejudiced comments predicted posting frequency.